Effects of fiber engraving laser on metallurgical, surface topography, and corrosion properties of AZ80 magnesium-based alloy - Narges Ahmadi; Homam Naffakh-Moosavy; Seyed Mohammad Mahdi Hadavi; Fatemeh Bagheri (Applied Surface Science Advances)
Surface modification with fiber lasers improves the biological and mechanical properties of biomaterials. Magnesium, a lightweight metal similar to natural bone, shows no toxicity and can aid in hard tissue recovery when implanted in the human body. However, its main drawback is its fast degradation rate in medical applications. Current research aims to study the effect of fiber lasers on the surface properties, metallurgical characteristics, and corrosion behavior of AZ80 magnesium-based alloy. The XRD and hardness test findings from the laser process show that some secondary phases have dissolved in the matrix, while others remain unchanged. The microhardness result for sample 4 indicated an increase to 120 HV with a loading force of 9.8 N at a holding time of 10 s. The roughness test showed a decrease from 10±0.54 µm for the AZ80 sample to 3.27±0.45 µm for sample 5. The results of the wettability test showed that the water contact angle increased from 55.1 ± 1.5° for AZ80 to 129 ± 4.3° for sample 3. The results of the polarization test showed changes in Ecorr from -1.55 mV to -1.63 mV and a shift in Icorr from 0.26 mA/cm² to 0.16 mA/cm². Sample 3 had three times higher resistance (R2 = 1710 Ω.cm²) compared to the laser-treated samples and AZ80 (R2 = 540.1 Ω.cm²). Laser-treated samples showed lower corrosion rates than untreated samples, thanks to a more uniform melted surface layer, lower roughness, and higher water contact angle. This method could enhance the corrosion resistance of the Mg-based AZ80 alloy in biomedical applications.